Neutrophils Kill Antibody-Opsonized Cancer Cells by Trogoptosis - Matlung, Hanke L.; Babes, Liane; Zhao, Xi Wen; van Houdt, Michel; Treffers, Louise W.; van Rees, Dieke J.; Franke, Katka; Schornagel, Karin; Verkuijlen, Paul; Janssen, Hans; Halonen, Pasi; Lieftink, Cor; et al. (Cell reports (Cambridge), 2018)
Destruction of cancer cells by therapeutic antibodies occurs, at least in part, through antibody-dependent cellular cytotoxicity (ADCC), and this can be mediated by various Fc-receptor-expressing immune cells, including neutrophils. However, the mechanism(s) by which neutrophils kill antibody-opsonized cancer cells has not been established. Here, we demonstrate that neutrophils can exert a mode of destruction of cancer cells, which involves antibody-mediated trogocytosis by neutrophils. Intimately associated with this is an active mechanical disruption of the cancer cell plasma membrane, leading to a lytic (i.e., necrotic) type of cancer cell death. Furthermore, this mode of destruction of antibody-opsonized cancer cells by neutrophils is potentiated by CD47-SIRPα checkpoint blockade. Collectively, these findings show that neutrophil ADCC toward cancer cells occurs by a mechanism of cytotoxicity called trogoptosis, which can be further improved by targeting CD47-SIRPα interactions. [Display omitted] •Neutrophils kill antibody-opsonized cancer cells by a process called trogoptosis•Cancer cell plasma membrane ingestion by neutrophils is instrumental in trogoptosis•Trogoptosis by neutrophils is further enhanced by CD47-SIRPα checkpoint inhibition Matlung et al. identify trogoptosis as an immune cell-mediated mechanism of cytotoxicity, demonstrating that neutrophil-mediated destruction of antibody-opsonized cancer cells occurs through a specific process that is distinct from that used by other immune cells.